Left Atrioventricular Coupling Index: A Novel Diastolic Parameter to Refine Prognosis in Heart Failure - Fortuni, Federico; Biagioli, Paolo; Myagmardorj, Rinchyenkhand; Mengoni, Anna; Chua, Anna P.; Zuchi, Cinzia; Sforna, Stefano; Bax, Jeroen; Ajmone, Marsan Nina; Ambrosio, Giuseppe; Carluccio, Erberto (Elsevier, 2025)
BACKGROUND: Left atrioventricular coupling index (LACI), an index coupling left atrial (LA) to left ventricular (LV) volume at end-diastole, showed to be associated with prognosis in different clinical settings. However, the relation between LACI and LV diastolic dysfunction (DD) remains to be established. The present study aimed to investigate the association between LACI and LV DD and to assess its prognostic value in patients with heart failure (HF).
METHODS: We retrospectively analyzed 1158 stable HF patients, on optimal medical therapy (derivation cohort). Clinical and echocardiographic features were characterized across LACI tertiles. The independent prognostic value of LACI (endpoint: all-cause death/HF-hospitalization) was assessed by Cox regression. Results were validated in an external cohort of 242 HF patients.
RESULTS: In the derivation cohort, the median LACI value was 0.29 (IQR:0.19-0.42). Patients in the third tertile (LACI>0.36) were older and presented with more advanced HF symptoms. While the prevalence of grade-1 DD (ASE/EACVI classification) progressively decreased across LACI tertiles, the prevalence of grade-3 DD significantly increased (8%,23%, and 46% respectively, P<0.0001). A cut-off value ≥0.26 identified moderate-to-severe DD with an area-under the-curve of 0.75. During follow-up (median 28 months, IQR:11-53), 407 (35%) patients reached the endpoint. On multivariable analysis, LACI was independently associated with outcomes (HR for 1-SD increase 1.16; 95%CI 1.06-1.28; P=0.002), showing incremental predictive value over the DD grading system (net reclassification improvement=0.150, P<0.0001). The prognostic value of LACI was consistent in the external validation cohort.
CONCLUSIONS: LACI is associated with DD severity and is an independent predictor of outcomes in HF patients.